2020
DOI: 10.33545/gynae.2020.v4.i2e.541
|View full text |Cite
|
Sign up to set email alerts
|

Uterine cavity coring before intra-uterine insemination in patients with unexplained infertility

Abstract: Introduction: Infertility, a major health problem nowadays, affects around 8-12% of couples worldwide. Unexplained infertility affects up to 15-30% of infertile couples. Management options for unexplained infertility are expectant management, timed intercourse, IUI with or without controlled ovarian stimulation, ART i.e IVF/intracytoplasmic sperm injection (ICSI). Endometrial mechanical injury in order to augment the probability of implantation of embryo and pregnancy rate has been particularly noted in recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The difference was statistically highly significant (p-value<0.0001). Dogra A et al 7 found that Mean endometrial thickness was comparable in both the cases (9.20 ± 3.37) and controls (9.16 ± 3.20). The difference was not statistically significant (p value=0.532).…”
Section: Discussionmentioning
confidence: 91%
“…The difference was statistically highly significant (p-value<0.0001). Dogra A et al 7 found that Mean endometrial thickness was comparable in both the cases (9.20 ± 3.37) and controls (9.16 ± 3.20). The difference was not statistically significant (p value=0.532).…”
Section: Discussionmentioning
confidence: 91%